Конечно-элементная модель деформирования биметаллической заготовки при получении вытяжкой коробчатых деталей - Гайкова, Татьяна Владиславовна (НТУ "ХПИ", 2016)
На основании метода конечных элементов смоделированы процессы вытяжки из биметалла алюминий-медь коробчатых деталей для различных типов заготовок. При моделировании использованы различные комбинации слоев материала, что позволяет судить о влиянии расположения слоев материала и формы заготовки на параметры процесса. Ориентируясь по моделям деформируемого состояния при получении коробчатых деталей из биметалла оптимальной формой для заготовки является "прямоугольник со срезанными углами" и внешним расположением слоя меди.

Based on the finite element method modeled processes extract from bimetal aluminum-copper box of parts for various types of workpieces. In the simulation used various combinations of layers of material that gives an indication of the impact location and the material layers to form the preform process. parameters. The intensity of the maximum voltage at the radius of curvature of the punch and reaches 350 MPa for the layer of copper and 260 MPa for the aluminum layer; a layer of copper is necessary to have the matrix, if permitted by manufacturing conditions, it reduces the intensity of the stresses in the layer of copper from 315 MPa to 250 MPa; used harvesting – a rectangle with beveled edges, decrease the maximum stresses and strains intensity from 315 MPa to 300 MPa, from 0.67 to 0.65 for the internal arrangement of copper and from 282 MPa to 250 MPa, from 0.63 to 0.59 for the external copper location; with a depth of 0.04 m εi = 0,56-0,; with increasing depth of the hood grow as the stress intensity and strain intensity (at a depth of 0.02 m proshtampovki εi = 0,3-0,375; σi = 200-230 MPa 67; σi = 300-315 MPa).
Certainly-element model of deformation of bimetallic purveyance at a receipt by extraction of box-type details
Keywords: конечно-элементная модель; биметалл; форма заготовки; вытяжка; интенсивность напряжений; деформирование; finite element model; bimetal; shape of the work piece; hood; stress intensity; deformation